2017
DOI: 10.1002/anie.201709744
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Depsipeptide BE‐43547A2: Synthesis and Activity against Pancreatic Cancer Stem Cells

Abstract: Asymmetric total synthesis of the cyclic depsipeptide BE-43547A was achieved in 15 linear steps on a 350 mg scale in one batch. The synthesis features the highly diastereoselective construction of an α-hydroxy-β-ketoamide through α-hydroxylation with a d.r. of up to 86:1. BE-43547A significantly reduces the percentage of pancreatic cancer stem cells (PCSCs) in Panc-1 cell cultures, and dramatically reduces the tumorsphere-forming capability of Panc-1 cells. An in vivo tumor-initiation assay, a gold standard fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…This resulted in a clear spectroscopic and chromatographic match to one of the synthetic diastereomers, which, along with CD spectroscopy, allowed us to determine both the relative and absolute configurations of the BE-43547 compounds. This assignment was subsequently validated by the Chen laboratory via the development of an alternative route to the same natural products . The biological activity of the APD-CLD compounds remains under investigation in our laboratory and elsewhere …”
Section: Syntheses Of Rakicidin a And Ent-be-43547a1mentioning
confidence: 82%
See 1 more Smart Citation
“…This resulted in a clear spectroscopic and chromatographic match to one of the synthetic diastereomers, which, along with CD spectroscopy, allowed us to determine both the relative and absolute configurations of the BE-43547 compounds. This assignment was subsequently validated by the Chen laboratory via the development of an alternative route to the same natural products . The biological activity of the APD-CLD compounds remains under investigation in our laboratory and elsewhere …”
Section: Syntheses Of Rakicidin a And Ent-be-43547a1mentioning
confidence: 82%
“…As already mentioned, several methods failed in the final dehydration to form the APD group from 26 , including standard, two-step, mesylation-elimination procotols, despite the fact that this approach works very well in closely related settings as demonstrated by our subsequent work on the BE-43547 class as well as a series of studies from the Yue Chen laboratory also targeting members of the APD-CLD class. , This failure, however, prompted us to perform a broad evaluation of alternative conditions for dehydration and the final use of the combination of N , N -disuccinimidyl carbonate (DSC) and NEt­( i -Pr) 2 to form the APD unit which presumably proceeds via the intermediacy of the mixed carbonate. In more recent work on synthetic derivatives of these natural products, we have found that other coupling reagents can also be used to generate the APD group and that this can even be performed with a concomitant amide coupling.…”
Section: Syntheses Of Rakicidin a And Ent-be-43547a1mentioning
confidence: 99%
“…A polysulfide solution (0.01 M) of Li 2 S 8 in 1,3‐dioxolane (DOL)/1,2‐dimethyoxyethane (DME) = 1/1 v/v ratio) was prepared; various types of carbon materials, such as pristine SPB and YP, and P‐doped ones (SPB@P and YP@P) were added to each solution with the same weight. [ 31,43 ] We observed the color of each solution and their characteristic absorption peaks from the UV–vis absorption profiles. As shown in the inset image of Figure 2f, the initial Li 2 S x solution had a dark yellow color, where S 8 peaks were observed at ≈560 nm in the UV–vis absorption spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…The rakicidin family members, together with vinylamycin, microtermolide A, BE-43547s, and boholamide A, all feature a 4-amino-2,4-pentadienolate (APD) moiety. These unique APD-cyclic depsipeptides exhibit particular cytotoxicity against cancer stem cells and selective inhibitory activities toward cancer cells under hypoxia conditions. With intriguing biological activities, these molecules have attracted the attention of chemists, including us.…”
mentioning
confidence: 99%
“…Based on our previous synthetic route of APD-cyclic depsipeptides, retrosynthetically, rakicidin C could be obtained from alcohol 2 . The hydroxy group and terminal amide in 2 should be temporarily protected, because of their liability. We selected the C-6 and N-1 amide bond for macrolactamization.…”
mentioning
confidence: 99%